THE STRATEGY OF HUMAN RESOURCES DEVELOPMENT IN IMPROVING THE COMPETITIVE ADVANTAGE (Case Study at Madinatul Qur'an Islamic Boarding School, Depok) - Jatmika, Agus; Entang, Muhamad; Purba, Jan Horas Veriady (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
This research aims to determine the strategy of developing human resources in increasing competitive advantage in the Madinatul Qur'an Islamic boarding school, Depok. Through the qualitative descriptive method, the result of the stages of the strategy is obtained. In the planning stage was done by formulating scientific building, capacity and character building. In the formulation stage generated aggressive strategy, namely involving target human resources as partners with various stimuli; refreshing through community service practices; growth strategy through building intellectual, religious, humanist and adaptive characters; defensive strategy through interdisciplinary and transdisciplinary training. Furthermore, the personal competency stage, through improving communication, managerial and business skills, the control stage that focuses on the uniqueness of tahfidz; the supervisory stage, in the form of optimizing the role of HR and the evaluation stage, in order to encourage the sensitivity of human resources to technological developments. The last is development stage, where Ma'had Aly graduates will be facilitated with a formal undergraduate education level to fulfil the demands of stakeholders. It can be concluded that the core resources targeted for human resource development are Ma'had Aly graduates. They are believed to be teaching staff who are devoted, adaptive to technological changes, sincere and trustworthy in carrying out their duties and obeying religious orders and memorizing the Qur'an. This is in accordance with the mission outcome of Madinatul Qur'an education base.